Dynamic response of single-layer reticulated shell with explosion-protection wall under blast loading - Su, Qianqian; Zhai, Ximei (Thin-walled structures, 2018)
To investigate the structural dynamic response of long span reticulated shell under external blast loading considering explosion-protection wall, explicit finite element (FE) programme LS-DYNA is used to set up the analytical model of explosion-protection wall corresponding to an experiment to grasp the propagation law of blast shock waves around the wall. The results of simulation and experiment are compared and the results verify the creditability and applicability of numerical simulation by using ALE (Arbitrary-Lagrange-Euler) algorithm. A Kiewitt8 single-layer reticulated shell of refinement with span of 40 m is established to simulate the responses of structure considering explosion-protection wall, which contains reticulated shell member, purlin hanger, purlin, rivet and roof boarding. According to simulation results from the maximum nodal displacement, average plastic strain and yielding degree of cross section of reticulated shell member, the dynamic response laws are proposed based on varying parameters, including height, position, length, material of the explosion-protection wall, rise-span ratio of reticulated shell and TNT explosive weights. Meanwhile, the influence rules of explosion-protection wall and structure on diffraction and reflection action of blast shock wave are obtained. In addition, the adverse height of the explosion-protection wall for reticulated shell with span of 40 m under external blast loading is proposed. Four damage types of reticulated shell with the explosion-protection wall subject to external blast loading are defined by summarizing all the structural response of FE numerical models, which could provide reference for reasonable explosion-proof design for reticulated shell structure. [Display omitted] •A FE model is developed using LS-DYNA and verified by experimental data.•The propagation of blast shock wave around explosion-protection wall is studied.•Adverse height of the explosion-protection wall for reticulated shell is proposed.•Dynamic response laws of reticulated shell with the wall are obtained.•Four damage types of reticulated shell with explosion-protection wall are defined.